Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 11 Data Analysis and Statistics - 11.2 Apply Transformations to Data - 11.2 Exercises - Mixed Review - Page 755: 27


See below

Work Step by Step

Given: $3x^2-13x+8=0$ We can see $a=3\\b=-13\\c=8$ Applying the quadratic formula, we found: $x_1=\frac{-(-13)+\sqrt (-13)^2-4(3)(8)}{2(3)}\approx3.59\\ x_2=\frac{-(-13)-\sqrt (-13)^2-4(3)(8)}{2(3)}\approx 0.7427$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.